Povezanost med vremenom in obiskom izbranih turističnih točk v Sloveniji - Vrtačnik Garbas, Katja (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2006)
Tourism is strongly connected with the weather, the climate and its changes. In this research we used data on the daily number of visitors of selected different types of tourist points in Slovenia to find out what the connection between the weather and the number of visitors is actually like. Furthermore, their responses give us an insight into the possible influences that climate changes, through changed weather patterns, might have on the variation of the number of tourists and daily visitors.
Keywords: vreme; weather; podnebje; climate; klimatske spremembe; tourism; turizem; recreation; rekreacija; Slovenia; Slovenija